2022
DOI: 10.3390/agriculture12111834
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Automatically Recorded Body Condition Scores with Measures of Production, Health, and Reproduction

Abstract: In the present study, we hypothesize that an automated body condition scoring system could be an indicator of health and pregnancy success in cows. Therefore, the objective of this study is to determine the relationship of the automated registered body condition score (BCS) with pregnancy and inline biomarkers such as milk beta-hydroxybutyrate (BHB), milk lactate dehydrogenase (LDH), milk progesterone (mP4), and milk yield (MY) in dairy cows. Indicators from Herd NavigatorTM were grouped into classes based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the thirty-sixth article [43], the authors hypothesised that an automated body condition scoring system could indicate health and pregnancy success in cows. Therefore, this study aimed to determine the association of automated recorded body condition score (BCS) with pregnancy and inline biomarkers, such as milk beta-hydroxybutyrate (BHB), milk lactate dehydrogenase (LDH), milk progesterone (mP4), and milk yield (MY) in dairy cows.…”
Section: Papers In This Special Issuementioning
confidence: 99%
“…In the thirty-sixth article [43], the authors hypothesised that an automated body condition scoring system could indicate health and pregnancy success in cows. Therefore, this study aimed to determine the association of automated recorded body condition score (BCS) with pregnancy and inline biomarkers, such as milk beta-hydroxybutyrate (BHB), milk lactate dehydrogenase (LDH), milk progesterone (mP4), and milk yield (MY) in dairy cows.…”
Section: Papers In This Special Issuementioning
confidence: 99%
“…Biosensors provide information regarding reproduction and health problems by detecting rumination, temperature, activity, and pH; furthermore, biosensors can monitor oestrus, pregnancy, and parturition (Bruinje and Ambrose 2019; Lee and Seo 2021). Since biosensors can detect mastitis, lameness, and metabolic disorders, they offer further understanding of these conditions (Rutten et al 2013;Bayne et al 2016;Haladjian et al 2018;Antanaitis et al 2020;Alipio and Villena 2022;Antanaitis et al 2022). However, to the best of our knowledge, no studies have reported data collected using biosensors in dairy cattle with JHS.…”
mentioning
confidence: 99%